2016
DOI: 10.5888/pcd13.150391
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Status and Being Up-to-Date on Colorectal Cancer Screening, 2012 Behavioral Risk Factor Surveillance System

Abstract: IntroductionAlthough screening rates for colorectal cancer are increasing, 22 million Americans are not up-to-date with recommendations. People with diabetes are an important and rapidly growing group at increased risk for colorectal cancer. Screening status and predictors of being up-to-date on screening are largely unknown in this population.MethodsThis study used logistic regression modeling and data from the 2012 Behavioral Risk Factor Surveillance System to examine the association between diabetes and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Although one of the proposed mechanisms explaining poorer cancer prognosis in diabetes patients is lower screening uptake [7], it may not be universally applicable. Indeed, some studies have shown higher participation of diabetes patients in colorectal [23] and prostate cancer [24] screenings. Whether diabetes patients are disadvantaged may depend on the prevalence of cancer screening in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although one of the proposed mechanisms explaining poorer cancer prognosis in diabetes patients is lower screening uptake [7], it may not be universally applicable. Indeed, some studies have shown higher participation of diabetes patients in colorectal [23] and prostate cancer [24] screenings. Whether diabetes patients are disadvantaged may depend on the prevalence of cancer screening in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetics are 22% more likely to be up to date with their CRC screening; however, having DM is an independent risk factor for inadequate bowel preparation [53, 6669]. This is most likely due to diabetics having slower gastric emptying and colonic transit [70].…”
Section: Diabetes Mellitus and Bowel Preparation For Colonoscopymentioning
confidence: 99%
“…We estimated multivariate logistic regression models to calculate odds ratios (ORs) for the odds of being up-to-date on CRC screening, adjusting for sociodemographic characteristics (age, gender, race/ethnicity, education, family income, employment, marital status, and census region), health insurance, smoking status, and comorbid conditions (hypertension, high cholesterol, heart disease, stroke, congestive heart failure, and renal failure). Because the greater frequency of provider visit increases the odds of CRC consultation ( Porter et al, 2016 ), we controlled for health services utilization (number of visits to physicians and non-physician providers) in our model. We set the P value for statistical significance at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the proven benefits of early detection ( Bibbins-Domingo et al, 2016 ), the uptake rate of CRC screening has been suboptimal ( Hong et al, 2017 ). It was estimated that about one-third of individuals aged 50 or older with diabetes, who met screening recommendations, reported not being up-to-date on CRC screening ( Porter et al, 2016 ). A recent study found that, among individuals with T2DM, the frequency of diabetes-related visits to care was not associated with receipt of CRC screening, suggesting that diabetic patients may not be referred for CRC screening despite the greater risk of CRC ( Porter et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation